Study of Clinical Variables Affecting Long Term Outcome after Microdisectomy for Lumbar Disc Herniation - Shrestha, D.; Shrestha, R.; Dhoju, D.; Kayastha, S.R.; Jha, S.C. (Kathmandu University Medical Journal, 2017)
Background Outcome of lumbar disc herniation are influenced by various clinical, socioeconomic and psychological factors. In the absence of provision of medical insurances, worker’s compensation and sick leave, predictors for outcome after lumbar disc herniation surgery will be different in Nepalese population. Objective To evaluate different clinical variables that can affect outcome after lumbar disc herniation surgery. Method Among 88 patients who underwent microdisectomy for lumbar disc herniation, 63 patients (43 male, 20 female) with follow up at least six months were retrospectively evaluated for clinical variables which can affect Oswestry disability index (ODI) score, its interpretation and Mcnab classification of post operative outcome. Result Average age of patients was 42.54±8.60 years. Mean follow up period was 34.89±23.80 months (range 6 -111 months). Thirty four patients had follow up period > 24 months. Mean ODI score before surgery and at final follow up was 37.87±8.76 vs 7.78±7.7; (p=0.00). Success rate was 90.47% (change in ODI score at least by 10), 93.65% (ODI score interpretation <40%), and 85.71%. (Mcnab outcome excellent and good). Significant correlation was found between age and ODI at final follow up but not with duration of symptoms. Male, non alcoholic, low level of education, numbness as a predominant symptom, disc at L4-L5 were significantly associated with better ODI at final follow up. For ODI score interpretation, gender, smoking habit, presence of leg pain as a predominant symptom were statistically significant factors whereas smoking and drinking habit, level of education, occupation, back pain and numbness as predominant pre-operative symptom, types of disc in MRI were significantly related to Mcnab outcome. There was 9.5% peri- or post-operative complications and recurrence in seven patients. Conclusion Age, gender, smoking and drinking habit, level of education, occupation, types of disc in MRI are important variables for ODI score, ODI score interpretation and Mcnab outcome.